Zimbabwean female participation in physics: the influence of identity formation on perception and participation - Gudyanga, Anna; Kurup, Raj (Cogent, 2019)
The study investigated the influence of identity formation on the perceptions and participation of Zimbabwean Advanced Level (A’ Level) female adolescent students in physics. Nine female adolescent students eighteen years and above: three doing mathematics and physics, one doing physics without mathematics and five doing mathematics without physics were purposively selected. The data generating instruments used were semi-structured interview and classroom observation guides as well as document analysis. Findings show that female students associate scientists within a masculine framework in a Eurocentric environment, specifically those scientists who are depicted in their textbooks. The female students doing physics had a positive physics identity which resulted in the formation of positive perceptions towards physics and their participation in the subject. The female students with a negative physics identity perceived physics, to be irrelevant to their future aspirations, difficult, too involving and masculine causing them not to opt for physics as one of their A’ Level subjects. Thus, the formation of a positive or negative physics identity by female adolescent students influences their positive or negative perceptions of physics and hence their participation or non-participation in the subject, respectively. We recommend that a wider and more comprehensive study nationally is warranted to confirm the findings of this study.